2023
DOI: 10.1080/15476286.2023.2293339
|View full text |Cite
|
Sign up to set email alerts
|

mRNA nuclear export: how mRNA identity features distinguish functional RNAs from junk transcripts

Alexander F. Palazzo,
Yi Qiu,
Yoon Mo Kang

Abstract: The division of the cellular space into nucleoplasm and cytoplasm promotes quality control mechanisms that prevent misprocessed mRNAs and junk RNAs from gaining access to the translational machinery. Here, we explore how properly processed mRNAs are distinguished from both misprocessed mRNAs and junk RNAs by the presence or absence of various ‘identity features’.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 178 publications
0
4
0
Order By: Relevance
“…It is known that in human protein-coding genes, GC-content peaks around the transcription start site (TSS) and slopes down into both the upstream intergenic region and downstream into the first exon and even the first intron (Xia et al, 2003; Louie et al, 2003; Zhang et al, 2004; Kalari et al, 2006; Haerty and Ponting, 2015; Zhu et al, 2009; Palazzo and Kang, 2021; Palazzo et al, 2024). We wanted to examine this GC-peak more closely by metagene analysis and compare it to other gene landmarks.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is known that in human protein-coding genes, GC-content peaks around the transcription start site (TSS) and slopes down into both the upstream intergenic region and downstream into the first exon and even the first intron (Xia et al, 2003; Louie et al, 2003; Zhang et al, 2004; Kalari et al, 2006; Haerty and Ponting, 2015; Zhu et al, 2009; Palazzo and Kang, 2021; Palazzo et al, 2024). We wanted to examine this GC-peak more closely by metagene analysis and compare it to other gene landmarks.…”
Section: Resultsmentioning
confidence: 99%
“…One of the most striking features of human protein coding genes is the pattern of GC-content present along its length (Palazzo et al, 2024; Palazzo and Kang, 2021). In particular, it has been observed that GC-content is highest at the 5’ end of genes, and that this decreases as one travels downstream and is lowest at the 3’ end of genes (Xia et al, 2003; Louie et al, 2003; Zhang et al, 2004; Kalari et al, 2006; Haerty and Ponting, 2015; Zhu et al, 2009; Palazzo and Kang, 2021; Palazzo et al, 2024). In addition, it has been observed that GC-content is higher in exons than in introns, with it being highest in the first exon and decreasing with every subsequent exon (Palazzo et al, 2024; Zhu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations